Nu-Crest, Corp. a production systems study - Godinez, Raquel Rosario Y.; Lopez, Marco Vincent; Maguyon, Anna Maria Assunta M.; Sugay, Paul Philip T.; Cruz, Rolan Paul K. (Diliman, Quezon City College of Engineering, 1993)
A highly effective and efficient production system at the heart of a manufacturing company enhances the productivity, and hence profitability, of the enterprise. To a great extent, this desired level of performance is dependent on management's planning, controlling, leading, and organizing this system to achieve the necessary dynamism. Therefore it is essential that a complete understanding of the system exists, in order to identify problems and constraints, to detect the causes and interactions of these problems, and to identify the proper solutions and recommendations which will contribute to the system's improvement. Nu-Crest, Inc., a batch manufacturing firm involved in the assembly and production of blinds and other extruded items, is operating at suboptimal performance. This is manifested primarily by noticeable lengthy lead times, in the delivery of goods to their customers. Visibly causing the unnecessary delays and inefficiencies in the system are: overstocked wastage; work-in processes; man and machine idle times; and breakdowns. The proponents of this study basically recommends a rescheduling of processes, and a reallocation of resources. Work tasks are combined and rearranged, revealing a more efficient product flow. Men are reassigned to other jobs, decreasing their original idle times. These introductions which are steps to JIT -- targeting zero inventory and producing what is needed -- are foreseen to radically reduce non-value adding activities, thus causing sooner delivery dates, allowing the company an opportunity in expansion of both their capacity and market share.
Submitted in partial fulfillment of the course requirements in IE 151 : Production System
Keywords: Nu-Crest Corporation; Manufacturing industry; Production engineering